Synthesis, Characterization, Cytotoxicity and Anticomplementary Activity of a Novel Dimethyltin(IV) Cyclobutyl Dicarboxylate Complex of 8-Hydroxyquinaldine - A.K. Al-Allaf, Talal; J. Rashan, luay (Asian Journal of Chemistry, 2010)
The reaction of equimolar quantities of dimethyltin(IV)-cyclobutyl dicarboxylate (prepared from dimethyltin(IV) dichloride and silver nitrate followed by addition of dipotassium cyclobutyl dicarboxylate) and 8-hydroxyquinaldine(L) in ethanol under reflux, afforded a novel complex of the formula . The complex was characterized by its elemental analysis and IR, NMR and mass spectral data. The complex was subjected to cytotoxic bioassay against one fluid suspension cell line, i.e., P338 and four solid cell lines, i.e., Hep-2, HeLa, L20B and RD using the MTT assay technique. It is also tested for its anticomplementary activity (using a test that detects complement proteins inhibition). These activities were compared with those of the reference standards, cisplatin, carboplatin and oxaliplatin as well as with those of the starting organotin compound against the same cell lines. The significance of these results is given and discussed.